5-8(s+1)=-9s+4

Simple and best practice solution for 5-8(s+1)=-9s+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-8(s+1)=-9s+4 equation:


Simplifying
5 + -8(s + 1) = -9s + 4

Reorder the terms:
5 + -8(1 + s) = -9s + 4
5 + (1 * -8 + s * -8) = -9s + 4
5 + (-8 + -8s) = -9s + 4

Combine like terms: 5 + -8 = -3
-3 + -8s = -9s + 4

Reorder the terms:
-3 + -8s = 4 + -9s

Solving
-3 + -8s = 4 + -9s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '9s' to each side of the equation.
-3 + -8s + 9s = 4 + -9s + 9s

Combine like terms: -8s + 9s = 1s
-3 + 1s = 4 + -9s + 9s

Combine like terms: -9s + 9s = 0
-3 + 1s = 4 + 0
-3 + 1s = 4

Add '3' to each side of the equation.
-3 + 3 + 1s = 4 + 3

Combine like terms: -3 + 3 = 0
0 + 1s = 4 + 3
1s = 4 + 3

Combine like terms: 4 + 3 = 7
1s = 7

Divide each side by '1'.
s = 7

Simplifying
s = 7

See similar equations:

| 6y-1= | | 0.3x-17=1.1x-25 | | 4/5x-1/5=9 | | 2(x+5)=36 | | 3x(x-2)+(x-2)= | | 3a+5+4a-6=2 | | x^2-10+11=0 | | -5-1.2= | | 2*log*x=log*2+log(3*x-4) | | 10+x-7x=-38 | | 8x+6(1+5x)=2 | | 6.1+1= | | 7+7k=147 | | 2/3m-1/3=5/12 | | 8-3y=2(3+y)-5 | | -2(n-4)=10-2N | | -2y-5+2y^2=0 | | 8x+6(1+5x)= | | 4-2(2w-3)=6w-90 | | -6-4=-7a-5 | | 5/2x=(x-5) | | y=3sinx+2cosx | | a+a+5.80+0.5(5.80+a)+3(0.5(5.80+a))=246.20 | | 5+3(n+1)=2n | | 5z^2(z^2+2)=24-16z^2 | | -6x+10=15-6x | | 3x(2+3y)= | | 5-4(10+8m)=39+5m | | (5x)/(3iy)=5-6i | | x(x+3)-6(x+3)=0 | | (y-x)(y+11x)=a^2-b^2 | | c+8+2c=-10 |

Equations solver categories